Falun Gong and Re-Education through Labor: Traditional Rehabilitation for the Misdirected to Protect Societal Stability within China’s Evolving Criminal Justice System - Bejesky, Robert (Columbia Journal of Asian Law, 2004)
Re-education through labor (RETL) is a form of administrative detention employed in China that is conducted outside of the formal criminal justice system and is designed to rehabilitate the behavior of societal “agitators.” It has been utilized more in recent years than in the past because flexibility in the formal criminal justice system has been diminishing with the modernization process. While Chinese officials have maintained that RETL is a necessary and effective device for sustaining societal harmony, mounting pressure prompted Beijing leaders in February 2003 to endorse new prohibitions on RETL administrators to improve the image of these centers. For the past four years, Falun Gong members have been the target of aggressive Chinese government crackdown and caught the attention of human rights group worldwide. The group was banned after being marked an “evil cult” on July 22, 1999. Some say the banning and crackdown occurred because of the fear that such a collective and solidified group could pose to the Chinese Communist Party (CCP) governance, while others maintain such measures were necessary to protect societal stability and public order from the harms that could emerge through diffusion of the group’s message and actions. The Chinese government has taken Falun Gong’s mobilization and expansion efforts very seriously. Human rights groups have been critical of China’s use of RETL and its treatment of Falun Gong members. In fact, Falun Gong filed a lawsuit in U.S. federal court that was supported in an amicus curiae brief by more than three dozen members of Congress, against former Chinese leader Jiang Zemin for acts of genocide on Falun Gong members. While this lawsuit was dismissed by the U.S. District Court in September 2003 pursuant to the doctrine of sovereign immunity, the dismissal likely did not spell the end of the controversy.